2020
DOI: 10.11607/ijp.6707
|View full text |Cite
|
Sign up to set email alerts
|

Implant-Supported Three-Unit Fixed Dental Prosthesis Using Coded Healing Abutments and Fabricated Using a Digital Workflow: A 1-Year Prospective Case Series Study

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Neither the difference in the bone loss within both groups between the mesial and the distal support, nor the difference between both groups for the distal supper was significant, but a significant difference was found between the bone level change in both groups at the mesial support. A recent systematic review, specifically on posterior three‐unit FDPs, revealed no publications on bone loss in tooth‐supported cases for comparison of the outcome, but results in the Implant‐group appear to be in line with other publications (Pol et al, 2018 , 2020 ). However, the clinical significance is limited, as the bone loss in both groups is too small to cause the loss of a supporting unit.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Neither the difference in the bone loss within both groups between the mesial and the distal support, nor the difference between both groups for the distal supper was significant, but a significant difference was found between the bone level change in both groups at the mesial support. A recent systematic review, specifically on posterior three‐unit FDPs, revealed no publications on bone loss in tooth‐supported cases for comparison of the outcome, but results in the Implant‐group appear to be in line with other publications (Pol et al, 2018 , 2020 ). However, the clinical significance is limited, as the bone loss in both groups is too small to cause the loss of a supporting unit.…”
Section: Discussionsupporting
confidence: 63%
“…This study aimed to address this shortcoming by building on methods suggested in the literature to measure radiographs in tooth‐supported cases (de Faria Vasconcelos et al, 2012 ; Misch et al, 2006 ; Vandenberghe et al, 2008 ). For teeth, measurement is hindered, as there is no easy way to calibrate between radiographs without an easily identifiable object of known and stable dimensions, while in implant cases, radiographic measurements can be calibrated by using the stable implant dimensions (Pol et al, 2020 ; Sewerin, 1990 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this may be that multi-span implant-retained reconstructions lack unilaterally antagonistic pairs for a secure positional relationship of the jaws to each other, depending on the individual patient situation. Based on the present findings, it can only be speculated whether the reason for the need for clinical modifications of the iFDPs is the technical process itself or the patient-specific situation affecting the bite registration [ 13 ]. The typical indication for an iFDP is the rehabilitation of posterior free-end situations to reestablish masticatory function without the need for removable dental prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of standardized scan bodies makes the IOS technology predestined for therapy with fixed implant reconstructions. Whereas in single restorations, secure occlusion is usually ensured by the adjacent teeth, in multi-unit implant-supported fixed dental prostheses (iFDP), the lack of stable occlusal support poses the challenge for IOS systems during computerized bite registration [ 13 ]. It is not the optical resolution of the IOS devices or the power of the software that are the limiting features, rather that the missing occlusal units become the bottleneck in digital impression taking for iFDPs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%